Decision making & discounting rates for self and others. - See, Xin Li. (2013)
In order to access the differences in decision making when people make decisions for themselves and Others, we carried out an experiment to find out firstly their perceived value of future rewards (i.e. choosing between $10 now or $30 a month later) and subsequently compare that to when making the same decision for Others. In our experiment, participants were told to make hypothetical monetary decisions for themselves and on a separate occasion told to make similar decisions on behalf of Others. In this study, we aim to find out 1) the variability in discounting rates when people make decisions for themselves, 2) the average discounting rates when people make decisions for Others, 3) any significant differences in discounting rates when making decisions for themselves vs. Others. Our research findings provided a generalized basis for in-depth future research on temporal discounting. Various implications are also discussed, as findings portray the differences in decision making when making decisions for Self vs. Others.